2007
DOI: 10.1002/nag.665
|View full text |Cite
|
Sign up to set email alerts
|

DEM analysis of the crack propagation in brittle clays under uniaxial compression tests

Abstract: SUMMARYThe discrete element method (DEM) has been used to study how cracks propagate in a continuum material (clay) subjected to a uniaxial compressive stress. The DEM results were compared with those obtained in laboratory samples. The laboratory tests used stiff clay samples with one crack inclined at varying angles with respect to the compressive stress. The DEM and the laboratory results compared very well. Also, the DEM proved to be a very successful approach for the visualization of secondary crack forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
24
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(26 citation statements)
references
References 14 publications
2
24
0
Order By: Relevance
“…In addition, the discrete element method (DEM) developed by Cundall and Strack (1979) has been applied to simulate growth of cracks in brittle clay specimens (Vesga et al 2008), showing good agreement with experimental results. The particle flow code (PFC) is a type of DEM, which is commercially available and has been applied to solve crack problems (Yoon 2007;Lee and Jeon 2011;Zhang and Wong 2012).…”
Section: Introductionmentioning
confidence: 91%
“…In addition, the discrete element method (DEM) developed by Cundall and Strack (1979) has been applied to simulate growth of cracks in brittle clay specimens (Vesga et al 2008), showing good agreement with experimental results. The particle flow code (PFC) is a type of DEM, which is commercially available and has been applied to solve crack problems (Yoon 2007;Lee and Jeon 2011;Zhang and Wong 2012).…”
Section: Introductionmentioning
confidence: 91%
“…It successfully modeled the global failure of a rock specimen as well as local cracking at the flaw tips (Li et al, 2005;Tang et al, 2001;Tang and Kou, 1998). In addition, DEM (Discrete Element Method) developed by Cundall and Strack (1979) was used to simulate the cracking process in brittle clay specimens (Vesga et al, 2008) and revealed a good agreement with the experimental results. They used PFC 2D (Particle Flow Code in two Dimensions) which can reproduce the cracks directly by bond breakage between the circular particles instead of using fracture mechanics theories where complex mathematical equations relevant to the stress intensity factor and fracture toughness at the crack tips are implemented.…”
Section: Introductionmentioning
confidence: 94%
“…The circles represent individual particles, while the lines are gradients of particle motion. 7 Thus, nodes and anti-nodes of vibration modes can well be detected. Characteristic functions ψ 1 , ψ 2 , ψ 4 , ψ 5 , ψ 6 , ψ 8 , ψ 9 and ψ 12 are very similar to linear eigenmodes of transverse beam vibration.…”
Section: Karhunen-loève Decompositionmentioning
confidence: 97%
“…In addition, KL decomposition of the simulated motion of the DEM model also reveils symmetric and asymmetric forms of combined transversal and longitudinal motion, as captured by characteristic functions ψ 3 , ψ 7 , ψ 10 and ψ 11 . 7 The length of the lines represent the displacements qualitatively. …”
Section: Karhunen-loève Decompositionmentioning
confidence: 99%
See 1 more Smart Citation